The Combined Antibacterial Mechanism of Ferulic Acid and ε-Polylysine Hydrochloride in Shewanella putrefaciens and the Effect of Their Application on the Storage Quality of Refrigerated Crayfish (Procambarus clarkii) with Plasma-Activated Water - Yue Cui; Tengteng Zhang; Dandan Zhao; Sai Gao; Yinchu Liu; Xinyu Yang; Han Lu; Xiaoguang Gao (Foods)
This study aimed to investigate the mechanism underlying the synergistic antimicrobial effect of ferulic acid (FA) and ε-polylysine hydrochloride (PL) on Shewanella putrefaciens (S. putrefaciens) and their application on crayfish (Procambarus clarkii). The treatment with FA and PL exhibited a strong synergistic inhibitory effect against S. putrefaciens. The combination of 1/4 Minimum Inhibitory Concentration (MIC) FA and 1/4 MIC PL was the most effective, damaging the cell structure and inhibiting the growth of S. putrefaciens. Plasma-activated water (PAW) can induce microbial inactivation through physical action. In addition, treatments with FA, PL, PAW, PAW-FA, PAW-PL, and PAW + PL-FA substantially decreased total viable counts (TVCs), total volatile base nitrogen (TVB-N), the thiobarbituric acid value (TBA), and the juice loss rate of crayfish, with FA-PL showing the best effect. This study confirmed the antimicrobial efficacy of PL, FA, and PAW, indicating their potential as effective preservatives for controlling spoilage in freshwater crustaceans.